United Arab Emirates : Detailed Assessment Report on Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report, 2008)
This paper highlights the detailed assessment report on antimoney laundering (AML) and combating the financing of terrorism in the United Arab Emirates (UAE). The AML law needs to be amended to expand the range of predicate offences and to provide greater powers for the financial intelligence unit. The authorities have taken positive initiatives to address the issue of Hawala dealers, and have introduced a voluntary system of registration and reporting. The central bank intends progressively to formalize its oversight regime for this sector.